Chapter 48 In Vivo Bioluminescence Imaging to Assess Compound Efficacy Against Trypanosoma brucei - Ritchie, Ryan (Springer Nature, 2020)
Traditional animal models for human African trypanosomiasis rely on detecting Trypanosoma brucei brucei parasitemia in the blood. Testing the efficacy of new compounds in these models is cumbersome because it may take several months after treatment before surviving parasites become detectable in the blood. To expedite compound screening, we have used a Trypanosoma brucei brucei GVR35 strain expressing red-shifted firefly luciferase to monitor parasite distribution in infected mice through noninvasive wholebody bioluminescence imaging. This protocol describes the infection and in vivo bioluminescence imaging of mice to assess compound efficacy against T. brucei during the two characteristic stages of disease, the hemolymphatic phase (stage 1) and the encephalitic or central nervous system phase (stage 2).